Monitoring handgrip strength to motivate lifestyle choices for patients with diabetes type 2 - a pragmatic randomised controlled trial - Lena Bornhöft; Susanne Bernhardsson; Lena Nordeman; Anna Grimby-Ekman; Maria Dottori; Maria E. H. Larsson (Taylor & Francis Group, 2024)
Physical strength can be an important parameter to monitor for patients with diabetes mellitus type 2 (T2DM) to promote healthy lifestyle choices. Functional measurements can contribute to healthcare advice and possibly motivate more active lifestyles. The aim of the study was to investigate whether adding measurement and feedback concerning handgrip strength (HGS) to the parameters measured for patients with T2DM at annual check-ups leads to change in physical activity (PA) level, HGS, HbA1c or waist circumference.Methods Measurement of HGS with Jamar dynamometers was added to annual check-ups for patients with T2DM by diabetes nurses in primary care with feedback about normal values for age and sex in the intervention group. The control group had standard check-ups. Change in self-reported PA level was measured with questionnaires.Results Seven clinics and 334 patients participated. The intervention led to similar effects on PA in both groups. Patients with T2DM had comparable HGS to the general public. Regression analyses showed statistically significantly higher HGS in the intervention group than in the control group at follow-up and no improvement in PA, HbA1c, or waist circumference. Increased HGS was found for older people, men, and people with normal-to-high inclusion HGS, while patients with low inclusion HGS reduced their strength levels.Conclusions Measuring HGS and giving feedback to patients with T2DM can lead to increased HGS but does not seem to affect general PA level, HbA1c, or waist circumference. People over 65 years, men, and people with normal-to-high HGS were influenced positively by the intervention. Patients with low HGS may need personalised support to increase physical activity and improve function.ClinicalTrials registration: NCT03693521